ANALYSIS OF THE DRIVERS OF LIVELIHOOD DIVERSIFICATION STRATEGIES AMONG SETTLED AGROPASTORALISTS IN GOMBE STATE, NIGERIA - David, H. S.; Egwuma, H.; Gomina, A.; Madaki, M. J.; Hassan, B. K. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study analysed the drivers of livelihood diversification strategies among settled agropastoralists in Gombe State, Nigeria. Multistage sampling procedure was employed to select 316 settled agropastoralists and data were collected through the administration of structured questionnaires. Descriptive statistics and Multinomial Logit regression were used to analyse the data. The results revealed that more than half (52%) of the respondents relied solely on on-farm activities, while 30%, 10% and 8% were engaged in a combination of on-farm and non-farm, on-farm and off-farm and on-farm, off-farm and non-farm activities, respectively, as livelihood diversifying strategies. The results also revealed that most (97%) of the respondents were male. The mean age of the agropastoralists based on their livelihood strategies was 42, 45, 45 and 47 years for the livelihood categories. Married individuals were more involved in the combination of on-farm and non-farm strategies (97%) and on-farm (92%). Those with formal education have greater involvement in diversified strategies. Agropastoralists with over 20 years of residence were more involved in diversified livelihood strategies, and larger households were more inclined towards on-farm strategies (53%), with a mean of 12 members. The result of the Multinomial Logit analysis showed that livelihood diversification strategies were determined by the age of household head (p< 0.05), education status (p< 0.05), period of residence (p< 0.10), dependency ratio (p< 0.10), extension contacts (p< 0.01), membership of cooperative (p< 0.10) and access to credit (p< 0.01). The study concludes that agriculture remains the dominant livelihood source among the sampled agropastoralists. It is recommended that the government, non-government agencies and relevant stakeholders enhance agricultural extension services and develop quality education and vocational training programmes to encourage agropastoralists’ participation in off-farm and non-farm livelihood diversification activities.